Literary Traditions: English in Malaysia and Singapore (Column 6) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
There is also the problem of confidence for young writers, who could hardly see the value of their writing even in a positive environment. The problem is greatly compounded when the threat of rejection is palpable to them, and when they cannot even properly figure out whether it would be worthwhile to write and publish in English in a country where literary activities in the language are deliberately marginalised and treated with the reduced status of “sectional literature.” Dina Zaman sums up the problem of English writing in Malaysia, especially for younger writers: I suppose my writing in English initially unsettled a few scholars and academics. When I began writing in the 90s academics kept asking me why I wrote in English and not Malay. I'm Malay and I should write in Malay…. In general, writing in Malaysia tends to be the domain of Malay writers. I have to admit when I think of writers, I think of Pak Samadetc first, then K.S. Maniam. This has nothing to do with the quality of their writing, but because of what we were told/informed. The pressure to write in Malay is of course not on Malay writers alone but on all Malaysian writers, although the Malay writers feel it more acutely owing to the risk of being singled out as traitors to the culture. After all, the logic goes, Malay is the national language and there are so many personal benefits for the writer, from economic to cultural, for writing in it, so why should a Malay writer choose not to write in the language? And the extent to which writing in English involves marginalisation and invisibility is obvious from Dina's statement; a writer in English herself, she cannot help but think that a writer in Malaysia means a writer in the national language first. That is how the political and cultural machinery works against the writers in English in the country and the net result is, as I have suggested earlier, the “othering” and exclusion of writings in English and an interrupted, slow growth of the tradition.